Strategi Komunikasi Pemasaran Mamavie Cake dan Café dalam Meningkatkan Penjualan - Azhary, Sephia Zahramita; Barus, Rehia Karenina Isabella (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study analyzes Mamavie Cake and Café's marketing communication strategy in increasing sales and maintaining customer loyalty amid fierce business competition. The approach used in this study is qualitative descriptive, with data collection techniques in the form of observation, in-depth interviews, and literature studies. The data was analyzed using the Huberman and Miles model, which included data reduction, data presentation, and a conclusion drawn. The results of the study show that the use of social media, especially Instagram and TikTok, is the main strategy in increasing customer engagement. Collaborations with influencers, creative promos, and interactive events also contribute to strengthening the brand image and attractiveness of the café. Despite facing challenges such as stiff competition and rapid changes in digital trends, continuous innovation and loyalty programs are a strategic step in retaining customers. Thus, Mamavie Cake and Café's marketing communication strategy has proven to be effective in driving business growth.